The Causes of Upper Gastrointestinal Bleeding in the National Referral Hospital: Evaluation on Upper Gastrointestinal Tract Endoscopic Result in Five Years Period - Ari Fahrial Syam; Murdani Abdullah; Dadang Makmun; Marcellus Simadibrata; Dharmika Djojoningrat; Chudahman Manan; Abdul Aziz Rani; Daldiyono Daldiyono (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2005)
Backgrounds: Gastrointestinal bleeding such as hematemesis or melena are common conditions in clinical practice and endoscopic service. The mortality rate due to gastrointestinal bleeding is relatively high. In this study, we evaluate the causes of hematemesis melena for the last 5 years and the factors associated with the bleeding. Methods: The study was done retrospectively. We obtained data from medical record of patients that performed endoscopy of upper gastrointestinal tract in Division of Gastroenterology, Department of Internal medicine, Cipto Mangunkusumo hospital (Jakarta, Indonesia) during the period of 2001 to 2005. Results: Of 4.154 patients who underwent upper gastrointestinal tract endoscopy from 2001 to 2005, we found that 837 patients (20.1%) were due to upper gastrointestinal bleeding. They were 552 male (65.9%) and 285 female patients (34.1%). Mean age of male patients was 52.7 ± 15.82 years, while for female patients was 54.46 ± 17.6 years. Of 837 patients who came due to hematemesis were 150 patients (17.9%), melena were 310 patients (37.8%), both melena and hematemesis were 371 patients (44.3%), 557 cases (66.5 %) due to non varices. Endoscopic results showed that 280 cases (33.4%) were due to esophageal varices. In general, this study had demonstrated that esophageal varices was the most frequent cause of upper gastrointestinal bleeding. We found 229 cases of esophageal varices were coincidence with portal hypertensive gastropathy. While ulcer was found in 225 cases (26.9%) and most of them were gastric ulcer (51.1%). Of gastrointestinal bleeding caused by esophageal varices, most were grade III in 138 cases (49.3%). The incidence of bleeding of bleeding were found more frequently in patients age group of 40 - 60 years (389 cases; 46.5%), 60 years (305 cases; 36.2%), 40 years (242 cases; 16.8%). The causes of bleeding in patients whose age 60 years, most were caused by ulcer (37.4%). In this study, we also found that cancer as the cause of gastrointestinal bleeding in 26 cases (3.1%). Gastrointestinal cancer comprised of gastric cancer in 15 cases (57.7%), duodenal cancer in 7 cases (26.9%), and esophageal cancer in 4 patients (15.4%). Conclusion: The most frequent cause of upper gastrointestinal bleeding was esophageal varices and usually had reached stage III. The non variceal cause of bleeding was gastric cancer. Upper gastrointestinal malignancy was also found to be the etiology of bleeding in this study. Keywords: upper gastrointestinal bleeding, endoscopy